Evaluating the influence of chemical composition and morphology of waxes on the fusion behaviour of rigid PVC - Johannes Lodewiekus Barnard; Divann Dale Robertson; Albert Johannes van Reenen (eXPRESS Polymer Letters)
A set of linear Fischer-Tropsch (FT) waxes were oxidized to various degrees by utilizing an ozonolysis method. These waxes were comprehensively characterized in terms of their chemical composition, thermal behaviour, molecular weight distributions, and overall polarity using various analytical techniques, including Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance spectroscopy (NMR), differential scanning calorimetry (DSC), high temperature size exclusion chromatography (HT-SEC) along with normal and reverse-phase high temperature solvent gradient interaction chromatography (HT-SGIC). Application-based studies were performed by evaluating the behaviour of these waxes in unplasticized polyvinyl chloride (uPVC) formulations. Analyses included hot melt mixing, single screw extrusion, scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS), and torque rheometry. Through a combination of these techniques, the lubrication mechanism of these waxes could be explained by the Rabinovitch model. It was found that a combination of molecular size and degree of polarity play a vital role in the migration of the waxes and therefore ultimately impacts the fusion behaviour of the overall polyvinyl chloride (PVC) formulation. Results indicate that fusion times can greatly be altered when using oxidised waxes, and this could be promising for the development of multifunctional lubricant systems.